“I Notice My Feelings:” Exploring Mindfulness with 1st Graders and their Families - Katie Schrodt; Zachary Barnes; Megan DeVries; Jennifer Grow; Pauli Wear (Networks: An Online Journal for Teacher Research, 2019)
This paper explores a study completed with 1st grade students while a five-week mindfulness unit was implemented in their classroom. The paper discusses tactics for teaching mindfulness strategies to students and results observed in the students over the course of the five-week study. It also contains journal entries completed by students and their families both in the classroom and at home.
Keywords: mindfulness; literacy; first grade